2018
DOI: 10.3390/ma11030346
|View full text |Cite
|
Sign up to set email alerts
|

Residual Tensile Strength and Bond Properties of GFRP Bars after Exposure to Elevated Temperatures

Abstract: The use of fiber reinforced polymer (FRP) bars in reinforced concrete members enhances corrosion resistance when compared to traditional steel reinforcing bars. Although there is ample research available on the behavior of FRP bars and concrete members reinforced with FRP bars under elevated temperatures (due to fire), there is little published information available on their post-fire residual load capacity. This paper reports residual tensile strength, modulus of elasticity, and bond strength (to concrete) of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(30 citation statements)
references
References 25 publications
0
20
0
1
Order By: Relevance
“…When the exposure temperature exceeded 300 °C, the ultimate tensile strength of GFRP bars was about 46% lower than that at room temperature (25 °C). The test results of Devon et al [ 21 ] indicated that the residual tensile strength of GFRP bars at 400 °C was 83% of that at room temperature, which is highly different from Reference [ 20 ] with the decrease of 46% of the tensile strength of GFRP bars at 300 °C. Similarly, Wang et al [ 22 ] found that the ultimate tensile strength of GFRP bars was reduced by a maximum of 6% at less than 80 °C, and by 22% at 80–120 °C.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…When the exposure temperature exceeded 300 °C, the ultimate tensile strength of GFRP bars was about 46% lower than that at room temperature (25 °C). The test results of Devon et al [ 21 ] indicated that the residual tensile strength of GFRP bars at 400 °C was 83% of that at room temperature, which is highly different from Reference [ 20 ] with the decrease of 46% of the tensile strength of GFRP bars at 300 °C. Similarly, Wang et al [ 22 ] found that the ultimate tensile strength of GFRP bars was reduced by a maximum of 6% at less than 80 °C, and by 22% at 80–120 °C.…”
Section: Introductionmentioning
confidence: 90%
“…When the temperature reached 350 °C, the tensile properties of both FRP bars were drastically reduced and the bearing capacity was almost lost. Therefore, due to different factors such as production process and level, resin types, fiber types, heating curve, and period of heating, the properties of FRP bars showed different degrees of deterioration after elevated temperatures [ 21 , 22 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…This is similar to the temperature ranges applied in the studies by Cao et al [33] and Chowdhury et al [34]. Meanwhile, the exposure time is determined based on the studies by Bazli et al [12], Li et al [14], and Ellis et al [16]. After heating for two hours, the test specimens were naturally cooled down prior to direct tensile test.…”
Section: Experimental Programmentioning
confidence: 95%
“…Many studies have been experimentally carried out to investigate the effect of high temperature on the mechanical performances of FRP composites [13][14][15][16][17][18][19][20][21]. Obviously, the mechanical properties of the FRP composites could be characterized by tensile, compressive, flexural impact, and interlaminar shear strength (ILSS) performances.…”
Section: Introductionmentioning
confidence: 99%
“…Soil nails are in contact with the surrounding soil through the mortar along the length direction, and the strength and stiffness of the undisturbed soil are improved via the bonding frictional resistance on the contact surface. Glass fiber reinforced polymer (GFRP) is lightweight as well as easily designed and processed and has high strength, fatigue resistance, and corrosion resistance, thereby representing a reasonable alternative to steel reinforcements [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%